Pendampingan Kepada Siswa untuk Meningkatkan Semangat Belajar di Masa Pandemi Covid-19 - Pudin; Ratna Dewi; Rifki Arif Nugraha; Salman Sunardi (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Learning assistance is a primary need for students who are already very bored in dealing with online learning. Learning mentoring activities will be able to increase student motivation in learning. So with that, a program that can help partners is prepared, namely the students of SDN Sangkanwangi 1 with a mentoring method that is relaxed and fun. The implementation of this activity is carried out regularly at SDN Sangkanwangi 1 for 30 days. These activities include providing motivation, materials, questions and answers, games, and rewards for students who actively participate. This activity is expected to increase student saturation in online learning during the pandemic.